IMPLEMENTASI DAN TANTANGAN PRINSIP TRANSPARANSI, AKUNTABILITAS, DAN KEMANDIRIAN DALAM TATA KELOLA BADAN USAHA MILIK NEGARA: KAJIAN PUSTAKA SISTEMATIS DALAM MENDORONG EFEKTIVITAS DAN KEBERLANJUTAN ORGANISASI - Gunawan Widjaja (CV. Adiba Aisha Amira, 2025)
This study conducts a systematic literature review of the implementation of the principles of transparency, accountability, and independence in the governance of State-Owned Enterprises (SOEs) in Indonesia, with a focus on their contribution to organisational effectiveness and sustainability. Through literature analysis, significant progress was found through the SOE Ministerial Regulation PER-01/MBU/2011 and digital transformations such as the GRC system at PT Pertamina, which increased the average GCG Rating score to 3.5/5 in 2024. However, key challenges include political intervention (65% of corruption cases related to political affiliations), bureaucratic culture, and policy uncertainty, which hinder management independence. Recommendations include reforming the Board of Commissioners to be 50% independent, establishing a Single SOE Data Portal, and mandatory GCG certification to achieve a score of 4.5/5 by 2027, in order to strengthen the global competitiveness of SOEs.